2021
DOI: 10.35445/alishlah.v13i2.974
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Covid-19 Pandemic on Students’ Learning Outcome in Higher Education

Abstract: The current Covid-19 pandemic has had many effects on human life globally, including the implementation of education. This study aimed to obtain the impact of the Covid-19 pandemic on learning outcomes in higher education. The research method used is a cross-sectional study. The data were taken from the test results at the end of the lecture, observations, and interviews. The research was conducted at the University of Muhammadiyah Lampung, IPDN Jatinangor Campus, and the Ahmad Dahlan Institute of Technology a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
1
1
1
3
Order By: Relevance
“…It is in line with Panigrahi, Srivastava, & Sharma's (2018) study where they found the integration of online learning with virtual communities could boost the students' learning outcomes better. However, it is in contrast to what Rahman (2021) did in his study stating that the students from three universities had a decrease in their learning outcomes during the Covid 19 pandemic. When compared to the students' learning outcomes they had in the face-to-face situation, data showed no significant difference between the on-campus and online learning groups of students in their learning outcomes (Holmes & Reid, 2021).…”
Section: Discussioncontrasting
confidence: 87%
“…It is in line with Panigrahi, Srivastava, & Sharma's (2018) study where they found the integration of online learning with virtual communities could boost the students' learning outcomes better. However, it is in contrast to what Rahman (2021) did in his study stating that the students from three universities had a decrease in their learning outcomes during the Covid 19 pandemic. When compared to the students' learning outcomes they had in the face-to-face situation, data showed no significant difference between the on-campus and online learning groups of students in their learning outcomes (Holmes & Reid, 2021).…”
Section: Discussioncontrasting
confidence: 87%
“…Andi Rahman dalam penelitiannya merekomendasikan perlunya kerjasama pendidik dengan berbagai pihak untuk membangun strategi pembelajaran dari sudut pandang siswa, serta perkembangan teknologi khususnya teknologi multimedia (Rahman, 2021). UQ saat ini telah memanfaatkan ICT dalam proses pembelajaran, namun masih dimanfaatkan untuk belajar mewarnai dan menggambar.…”
Section: )unclassified
“…Disamping itu kegiatan ini merupakan salah satu wujud kerjasama pendidik dengan akademisi (peneliti di Universitas) dalam mengembangkan serta menerapkan media pembelajaran dengan memanfaatkan teknologi seiring dengan perkembangan dan perubahan gaya belajar di era transformasi digital (Rahman, 2021).…”
Section: Gambar 2 Fitur Aplikasi Arcovidiaunclassified
“…Rahman'da (2021), Covid-19 pandemisinin yükseköğretimde öğrenme çıktıları üzerindeki etkisini belirlemek amacıyla yapmış olduğu çalışmasında 2020-2021 eğitim öğretim yılında öğrencilerin öğrenme çıktılarının 2019-2020 eğitim öğretim yılına göre düştüğü sonucuna varmıştır. Öğrenme çıktılarındaki bu düşüşün düşüş bilgi, beceri ve psikolojiyi içerdiğini ifade eden Rahman (2021) Pandemi döneminde üniversitelerde verilen mimarlık ve tasarım eğitimini gözlem, görüşme ve odak grup çalışmalarıyla elde ettiği verileri değerlendirdiği Reframing continuous assessment in architecture and design education for the post-pandemic age başlıklı çalışmasında Lörincz (2022), öğrencilerin bilgilerini sürekli olarak değerlendirmeye yönelik dört ana yaklaşımı ortaya koymaktadır. Bunlar: Portföy, rol oynama, etkileşimli yöntemler ve uygulamalı sınav.…”
Section: Online Tasarım Eğitimiunclassified